Customer Engagement in Utilitarian vs. Hedonic Service Contexts - Barrett (Sage, 2025)
In the last decade, customer engagement has become a key concept in service research. While the customer engagement literature has gained significant traction and is maturing, studies have predominantly focused on hedonic consumption contexts, such as social media platforms or brand communities. We argue that hedonic and utilitarian service services are fundamentally different. Therefore, existing research knowledge on customer engagement does not necessarily hold in more utilitarian contexts, such as healthcare or financial services, where greater customer engagement could increase societal and individual well-being. By synthesizing insights from the customer engagement literature and the literature on hedonic versus utilitarian consumption, we identify assumptions in customer engagement research that need revising. We extract five fundamental features that differ between hedonic and utilitarian services (affectivity, motivational focus, perception of necessity, role of risk, and relational focus). Based on these features, we derive propositions that describe the role of context for the drivers and outcomes of customer engagement, as well as their interrelationships, and provide guidelines for future research to augment the scope of customer engagement research. As its main contribution, this article problematizes the current premises of customer engagement research and demonstrates that assumptions held about customer engagement are not necessarily generalizable across contexts.